Acute subdural hematoma and diffuse axonal injury in fatal road traffic accident victims: a clinico-pathological study of 15 patients - Gusmão,Sebastião Nataniel Silva (2003)
OBJECTIVE: Although acute subdural hematoma (ASDH) and diffuse axonal injury (DAI) are commonly associated in victims of head injury due to road traffic accidents, there are only two clinico-pathological studies of this association. We report a clinical and pathological study of 15 patients with ASDH associated with DAI. METHOD: The patients were victims of road traffic accidents and were randomly chosen. The state of consciousness on hospital admission was evaluated by the Glasgow coma scale. For the identification of axons the histological sections of the brain were stained with anti-neurofilament proteins. RESULTS: Twelve of the 15 patients were admitted to hospital in a state of coma; in three patients, the level of consciousness was not evaluated, as they died before hospital admission. CONCLUSION: The poorer prognosis in patients with ASDH who lapse into coma immediately after sustaining a head injury, as described by several authors, can be explained by the almost constant association between ASDH and DAI in victims of fatal road traffic accidents.